Dying for a cause: NETosis, mechanisms behind an antimicrobial cell death modality - Remijsen, Q (Nature Publishing Group, 2011)
Neutrophil extracellular traps (NETs) are chromatin structures loaded with antimicrobial molecules. They can trap and kill various bacterial, fungal and protozoal pathogens, and their release is one of the first lines of defense against pathogens. In vivo, NETs are released during a form of pathogen-induced cell death, which was recently named NETosis. Ex vivo, both dead and viable neutrophils can be stimulated to release NETs composed of either nuclear or mitochondrial chromatin, respectively. In certain pathological conditions, NETs are associated with severe tissue damage or certain auto-immune diseases. This review describes the recent progress made in the identification of the mechanisms involved in NETosis and discusses its interplay with autophagy and apoptosis.